EFFECTS OF SOIL CHARACTERISTICS AND DATE PALM MORPHOLOGICAL DIVERSITY ON NUTRITIONAL COMPOSITION OF PAKISTANI DATES. (26th July 2016) - FATIMA, GHAYOOR; WIEHLE, MARTIN; KHAN, IQRAR AHMAD; KHAN, ASIF ALI; BUERKERT, ANDREAS
SUMMARY: The use of date palm ( Phoenix dactylifera L.) has been closely connected with the survival of people in arid areas given their fruits´ high concentration of energy, fibre, minerals, vitamins and 16 amino acids. The arid climate and sandy or clayey loam soils in many parts of Pakistan are ideal for the cultivation of date palm, which contributes to feeding the country's rapidly growing population. To fill knowledge gaps on the effects of cultivar diversity and cultivation sites on the nutritional properties of dates, the present project studied dates and related physical and chemical soil properties across six districts in four provinces of Pakistan: Jhang, Muzaffargarh and Bahawalpur in Punjab; Dera Ismail Khan (D. I. Khan) in Khyber Pakhtunkhwa (KPK); Khairpur in Sindh and Panjgur in Baluchistan. To this end, during 2012–2013, a total of 170 households (HHs) were selected using a snowball sampling approach. Thirty-nine different date palm cultivars with diverse nutritional properties are grown in the study area. In these total soluble solids (TSS) were highest in Muzawati and Koharba cultivars, while cultivars and site conditions significantly affected TSS, minerals (calcium and magnesium), acidity, and firmness of dates. Concentration of CaCO3 and bulk density (BD) of soils varied widely, while hydraulic conductivity (HC) was similar across sites ( p = 0.128). Mean soil pH was highest in Panjgur (8.3) and lowest in Muzaffargarh (7.6), soil organic matter content was highest in Jhang (0.8%) and lowest in D. I. Khan (0.6%) and plant available phosphorous (P) was highest in Muzaffargarh (7.8 mg kg −1 ) and lowest in Panjgur (6.0 mg kg −1 ). As indicated by correlation analysis BD and cation exchange capacity of soils seemed to affect TSS, whereas concentration of CaCO3 and available P were correlated with calcium concentration of dates. HC and electrical conductivity, however, seemed to have little effect on dates´ nutritional properties.